Workshop Pengenalan Bisnis Digital - Khairunnisa, Khairunnisa; Isynuwardhana, Deannes; Fahlevi, Ali Riza; Arfitsa, Fajra (Community Service Progress, 2025)
The rapid growth of digital technology has transformed how the younger generation interacts with the economy, particularly students at the vocational high school level. Students at SMK Santana 2 Cibatu, Garut—primarily from Office Automation and Software Engineering majors—demonstrate strong enthusiasm for digital tools but often lack structured knowledge about how to start and manage digital businesses. This community service program aims to enhance students’ entrepreneurial readiness through the “Digital Business Introduction Workshop.” The program was designed to provide practical training on digital business concepts, e-commerce, financial literacy, and ethical considerations in online commerce. The implementation included interactive seminars, hands-on workshops, and digital marketing simulations tailored to student needs. Results of the workshop showed increased digital business awareness, with many students expressing intent to create online shops and apply the concepts learned. This initiative not only supports digital entrepreneurship among vocational students but also contributes to reducing youth unemployment through skill-based empowerment, aligned with SDG 8 (Decent Work and Economic Growth).